2020
DOI: 10.1111/gcbb.12727
|View full text |Cite
|
Sign up to set email alerts
|

Assessing influence in biofuel production and ecosystem services when environmental changes affect plant–pest relationships

Abstract: Climate change is currently affecting both biodiversity and human activities; land use change and greenhouse gas emissions are the main drivers. Many agricultural services are affected by the change, which in turn reflects on the basic provisioning services, which supply food, fibre and biofuels. Biofuels are getting increasing interest because of their sustainability potential. Jatropha curcas gained popularity as a biodiesel crop, due to its ease of cultivation even in harsh environmental conditions. Notwith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…Climate change is also a driving factor that affects ecosystem services. Studies have shown that among the impacts of precipitation, management policies, terrain, and soil erodibility on soil conservation and water production, the impact of precipitation was greater [6,23]. The management policies related to human activities had relatively little impact on those services, and terrain had a greater impact on soil conservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change is also a driving factor that affects ecosystem services. Studies have shown that among the impacts of precipitation, management policies, terrain, and soil erodibility on soil conservation and water production, the impact of precipitation was greater [6,23]. The management policies related to human activities had relatively little impact on those services, and terrain had a greater impact on soil conservation.…”
Section: Discussionmentioning
confidence: 99%
“…As the link and bridge between ecosystems and social systems [2,3], ecosystem services are closely related to human wellbeing [4,5]. However, with the intensification of global climate change and increasing human activities, regional ecosystem service functions have undergone significant changes, affecting the sustainable development of regional ecology, economy, and society [6,7]. Especially, when human disturbance exceeds the tolerance of the ecosystem, the stability of the ecosystem structure can be destroyed, leading to ecological and environmental problems such as habitat fragmentation and ecosystem function degradation [8].…”
Section: Introductionmentioning
confidence: 99%
“…We performed future land-use-land-cover (LULC) simulations in sub-Saharan Africa using the InVEST suite, a geospatial modelling framework tool that evaluates the impact of land-use change on ES ( Sharp et al, 2018 ; De Simone et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…For both species, the percent contribution of each predictor was assessed, and the corresponding partial dependence plots were produced. The ensemble models (EMs) were then created from the single base models using the "BIOMOD_EnsembleModeling" function, selecting single models which performed with AUC > 0.80 and TSS > 0.70, thus obtaining a more "conservative" final EM (Iannella et al 2018;Cerasoli et al 2019a;De Simone et al 2020).…”
Section: Model Building and Evaluationmentioning
confidence: 99%
“…Climate is often regarded as the main abiotic factor shaping species' distributions both at broad (Root 1988;Buckley & Jetz 2007;Sexton et al 2009;Wiens 2011;De Simone et al 2020) and narrow (Iannella et al 2018;Brunetti et al 2019) spatial scales. Big climatic events, such as those that occurred during the Late Pleistocene and Holocene ages, have deeply influenced the distribution patterns of many animal and plant species, leading to large-scale range contractions, range expansions, and extinctions.…”
Section: Introductionmentioning
confidence: 99%